Anion-binding catalysis - García Mancheño, Olga (Wiley-VCH, 2022)
Explores the potential of new types of anion-binding catalysts to solve challenging synthetic problems Anion-Binding Catalysis introduces readers to the use of anion-binding processes in catalytic chemical activation, exploring how this approach can contribute to the future design of novel synthetic transformations. Featuring contributions by world-renowned scientists in the field, this authoritative volume describes the structure, properties, and catalytic applications of anions as well as synthetic applications and practical analytical methods. In-depth chapters are organized by type of catalyst rather than reaction type, providing readers with an accessible overview of the existing classes of effective catalysts. The authors discuss the use of halogens as counteranions, the combination of (thio)urea and squaramide-based anion-binding with other types of organocatalysis, anion-binding catalysis by pnictogen and tetrel bonding, nucleophilic co-catalysis, anion-binding catalysis by pnictogen and tetrel bonding, and more. Helping readers appreciate and evaluate the potential of anion-binding catalysis, this timely book: Illustrates the historical development, activation mode, and importance of anion-binding in chemical catalysis Explains the analytic methods used to determine the anion-binding affinity of the catalysts Describes catalytic and synthetic applications of common NH- and OH-based hydrogen-donor catalysts as well as C-H triazole/triazolium catalysts Covers amino-catalysis involving enamine, dienamine, or iminium activation approaches Discusses new trends in the field of anion-binding catalysis, such as the combination of anion-binding with other types of catalysis Presenting the current state of the field as well as the synthetic potential of anion-binding catalysis in future, Anion-Binding Catalysis is essential reading for researchers in both academia and industry involved in organic synthesis, homogeneous catalysis, and pharmaceutical chemistry.